Toxicity effects of an insecticidal soap on the green peach aphid [Homoptera: Aphididae] - Tremblay, Éléonore; Bélanger, André; Brosseau, Marcel; Boivin, Guy (Phytoprotection, 2009)
Effects of an insecticidal soap on the survival, development and reproduction of the green peach aphid, Myzus persicae, were studied. Twenty-four hours after application at a concentration of 37.50 g L-1, the soap caused 100% mortality in all aphid instars, and LC50 (lethal concentrations causing 50% mortality in the population) were 1.50, 3.25 and 5.50 g L-1 for first and second instars, third and fourth instars, and adult M. persicae, respectively. Aphids that survived the LC50 had a shorter longevity than the controls. Both insecticidal soap and parasitoids could be used on a crop but, as the LC50 of the third and fourth instars and adult M. persicae are higher than that of the aphid parasitoid Aphidius colemani (2.75 g L-1), it is essential to avoid treating aphids with insecticidal soap when adult parasitoids are present in the crop.